Optimal clinical management of children receiving dietary therapies for epilepsy: Updated recommendations of the International Ketogenic Diet Study Group. Issue 2 (21st May 2018) - Kossoff, Eric H.; Zupec‐Kania, Beth A.; Auvin, Stéphane; Ballaban‐Gil, Karen R.; Christina Bergqvist, A.G.; Blackford, Robyn; Buchhalter, Jeffrey R.; Caraballo, Roberto H.; Cross, J. Helen; Dahlin, Maria G.; Donner, Elizabeth J.; Guzel, Orkide; et al.
Summary: Ketogenic dietary therapies (KDTs) are established, effective nonpharmacologic treatments for intractable childhood epilepsy. For many years KDTs were implemented differently throughout the world due to lack of consistent protocols. In 2009, an expert consensus guideline for the management of children on KDT was published, focusing on topics of patient selection, pre‐KDT counseling and evaluation, diet choice and attributes, implementation, supplementation, follow‐up, side events, and KDT discontinuation. It has been helpful in outlining a state‐of‐the‐art protocol, standardizing KDT for multicenter clinical trials, and identifying areas of controversy and uncertainty for future research. Now one decade later, the organizers and authors of this guideline present a revised version with additional authors, in order to include recent research, especially regarding other dietary treatments, clarifying indications for use, side effects during initiation and ongoing use, value of supplements, and methods of KDT discontinuation. In addition, authors completed a survey of their institution's practices, which was compared to responses from the original consensus survey, to show trends in management over the last 10 years.